(untitled) (Research, Society and Development, 2020)
This integrative review aimed to know the scientific production on the impacts of the COVID-19 pandemic on the mental health of nursing workers. The review was carried out by two independent researchers. The selected articles were searched in the PubMed / MEDLINE database and, despite the use of MeSH terms, it was decided to select “all fields” at the time of the search to increase the number of articles found. Filters for the years 2019 and 2020 and Portuguese, Spanish and English were applied. Initially, 528 articles were found, of which 31 articles were selected, 17 of which came from research conducted in China. The nursing teams are composed mainly of women and, in the studies that dealt with health workers, most of the sample was composed of professionals from the nursing team. Several studies have found evidence that COVID-19 is causing some degree of mental distress in healthcare and nursing teams. In this new pandemic context, nursing teams face daily situations that directly impact their mental health. In this sense, it is essential to appropriate the scientific knowledge produced as a means of reconstructing new work processes in nursing and health.